The Influence of Educational Snakes and Ladders Game on the Cognitive Development of Children Aged 5-6 Years in TK Aisyiyah Bustanul Athfal 41 - Chayria Putri Pratami; Kamtini (Indonesian Journal of Advanced Research, 2023)
This study aims to find out how the educational snakes and ladders game influences the cognitive development of children aged 5-6 years at Aisyiyah Bustanul Athfal 41 Private Kindergarten. This research was conducted at Aisyiyah Bustanul Athfal 41 Private Kindergarten, with a population of 54 children and 15 children as a sample. who is in the Tulip class. The sampling technique used purposive sampling. In this study the method used was the Quasi Experimental Designs research method using the Equivalent Time Samples Design research design. The data collection instrument uses an observation sheet. The first treatment (X1) which was given treatment, the child obtained an average score of 7.4 included in the Less Good category. The second treatment (X0) which was not given child treatment obtained an average value of 6.3 included in the Not Good category. Furthermore, in the third treatment (X1) which was given treatment, the child got an average value of 13 included in the Very Good category. And finally the fourth treatment (X0) which was not given treatment, the child got an average value of 12.2 which was in the Good category. Based on the results of the Friedman test calculations, it shows the Asymp Value. Sig (0.000) < 0.05, it can be concluded that there is a significant effect of the educational snakes and ladders game on the cognitive development of children aged 5-6 years in TK Aisyiyah Bustanul Athfal 41.